Stability of Picard - S Iteration processes for ξ- Uniformly Accretive Mapping. (Journal of the College of Basic Education, 2022)
In this paper we study the stability and the strong convergence to unique fixed point of uniformly accretive mapping by using picard Iteration process in Banach space.